Ethnic Differences in Health Literacy Among Young Adults in Amsterdam - Iris M. Blom; Eva S. Cohen; Lola V. Eshuis; Anke J. Woudstra; Marieke B. Snijder; Anton E. Kunst; Mirjam P. Fransen (SLACK Incorporated, 2018)
Background: Ethnic differences in health commence early in life. Ethnic minority young adults have a greater prevalence of unhealthier lifestyles and poorer health outcomes than their peers. Variations in health literacy could contribute to these ethnic inequalities in health but have not yet been investigated in this group. Objective: This study investigated ethnic differences in performance-based and self-reported health literacy in young adults and examined whether these differences are explained by educational level, language difficulties, or cultural distance. Methods: Young adults (age 18-25 years) from Dutch, African Surinamese, South-Asian Surinamese, Ghanaian, Turkish, and Moroccan ethnic backgrounds (N = 2,215) participated in the HELIUS (HEalthy Life in an Urban Setting) study, a cohort study in Amsterdam, the Netherlands. Performance-based health literacy was measured by the Rapid Estimate of Adult Literacy in Medicine in Dutch (REALM-D). Self-reported health literacy was measured by the Chew's Set of Brief Screening Questions (SBSQ). The association between ethnicity and health literacy, and the role of background characteristics was assessed by linear regression analyses. Key Results: Performance-based health literacy was low (REALM-D <60; range, 0-66) among 17% of the participants. After adjustment for educational level, average levels of REALM-D were lower among participants from a Ghanaian, Turkish, and Moroccan background than those from a Dutch background, whereas the two Surinamese groups did not differ from the Dutch group. Additional adjustment for language difficulties and cultural distance did not explain the differences between the five ethnic minority groups. Self-reported health literacy was low (SBSQ <3; range, 0-4) among 3% of the participants. There were no differences in levels of SBSQ between the ethnic minority groups and the Dutch group. Conclusions: We found ethnic differences in performance-based health literacy, which largely remained after adjustment for educational level. Further research is needed to gain insight into how young adults from different ethnic groups appraise and apply health information in various contexts.